PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI IPA SMA NEGERI 5 PEKANBARU - Karenta, Relysa Karenta Relysa; Rery, R. Usman Rery Usman; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack : This research aimed to know the effectiveness of guided inquiry learning model in improving the student achievement in class XI IPA SMAN 5 Pekanbaru. This research was a quasi experiment with randomized group pretest-posttes design. The sample of this study was XI IPA 5 as experiment class and XI IPA 6 as control class after being tested for normality and homogeneity tests. Normality test was performed using Liliefors test. The results of the Liliefors normality test obtained for all the data (material prerequisites, pretest, and posttest) normal distribution where Lmaks ≤ Ltabel. The results of the homogeneity test, of Fhitung<Ftabel (1.23 <1.72 with α = 0.05, dk(36.36)) which means that the samples have the same variance (homogeneous). Data analysis technique used was t-test, obtained thitung≥ ttable (2.398> 1.67 with dk = n1 + n2 - 2 and α = 0.05) means that the application of guided inquiry learning model gave effect of 8.02% to the improvement of the student achievement. KeyWords :Guided Inquiry, student achievement, salt hydrolysis.